Everyday life and boredom of people living with dementia in residential long-term care: a merged methods study - Doris Gebhard; Julia I. Frank (BMC Geriatrics)
Abstract Background Everyday life in residential long-term care is widely portrayed as boring. However, empirical evidence on this topic remains limited, particularly for the vulnerable group of people living with dementia. A better understanding of everyday life and the associated experiences of boredom could facilitate the development of practical strategies to reduce boredom in this target group. The aim of this study is therefore to analyse everyday activities, daily routines and the frequency and types of boredom in people living with dementia in residential long-term care. Data and methods In five long-term care facilities, participants were observed for two days in 20-minute time slots (from 7 am to 7 pm) using the Maastricht Electronic Daily Live Observation Tool. Semi-structured interviews were conducted with people living with dementia about their daily routines and experiences of boredom. Qualitative content analysis based on Mayring was applied, using the five boredom types from Goetz et al. as deductive categories. Observational data was analysed descriptively and merged with qualitative data on daily routines. In all, 46 people living with dementia (average age: 84.65 ± 7.15 years, 89.13% female, average DSS: 6.50 ± 3.15) were observed at 2760 time points. Of these, 17 participants took part in the interviews. Results The residents spend 47.5% of their day doing nothing and follow a routine that is strongly determined by communal meals. 62.5% of participants are bored, with 18.5% describing boredom as a constant/prevalent condition in their everyday lives. All five types of boredom are reflected in the interviews, with apathetic boredom being the most common. Conclusions Although people living with dementia follow almost the same daily routine in residential long-term care, they experience everyday life very differently, ranging from no boredom, to feelings of pleasant relaxation when bored to strongly negative feelings such as hopelessness and frustration. These findings suggest that interventions to prevent or reduce boredom need to be personalised in order to effectively combat the highly individual nature of boredom. Person-centred dementia care provides a valuable intervention strategy to meet this requirement. Clinical trial number Not applicable.